2011
DOI: 10.1002/jmri.22645
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation/perfusion imaging of the lung using ultra‐short echo time (UTE) MRI in an animal model of pulmonary embolism

Abstract: Purpose To test the feasibility of ultra-short echo time (UTE) MRI for assessment of regional pulmonary ventilation/perfusion in a standard 3 Tesla clinical MRI system. Materials and Methods MRI of the lungs was conducted with an optimized three-dimensional UTE sequence in normal rats and in a rat model of pulmonary embolism (PE) induced by a blood clot. Changes in signal intensities (SIs) due to inhalation of molecular oxygen or intravenous (i.v.) injection of Gd, which represents the distribution of ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 38 publications
1
45
1
Order By: Relevance
“…The magnitude of the measurement uncertainty assessed in lung was markedly improved compared with that obtained with UTE‐VFA reported previously . The RSD measured with SIR‐UTE was 1.7%, compared with 11% that was achieved with UTE‐VFA.…”
Section: Discussionmentioning
confidence: 54%
“…The magnitude of the measurement uncertainty assessed in lung was markedly improved compared with that obtained with UTE‐VFA reported previously . The RSD measured with SIR‐UTE was 1.7%, compared with 11% that was achieved with UTE‐VFA.…”
Section: Discussionmentioning
confidence: 54%
“…Pleural effusion could be recognized in the very short TE images; however, because of low contrast between pleural effusion and the thoracic The visualization of pulmonary parenchyma at MR imaging remains problematic because physiologically perfused and ventilated lung parenchyma appears black on conventional MR images because of extremely fast decay of the transverse magnetization (17). Togao et al (11) reported on ventilation and perfusion imaging of the lung by using very short TE in a 3-T clinical MR imaging system. Their TE of 100 msec provided sufficient MR signal from the lung parenchyma to show pulmonary ventilation (by oxygen inhalation) or perfusion (by administration of gadolinium-based contrast material).…”
Section: Very Short Te Sequencesmentioning
confidence: 98%
“…Very short echo time (TE) with radial k-space sampling of the free induction decay has previously been proposed for lung imaging (11)(12)(13) with MR imagers up to 3-T field strength. TEs of 100 msec or less allow observation of MR imaging signal from lung tissue, which is undetectable by using conventional MR imaging techniques.…”
Section: Transplantation Proceduresmentioning
confidence: 99%
“…These problems were due to the breath-hold MR angiographic techniques; these require a long breath hold, which is particularly problematic for patients with dyspnea. Ultrashort echo time (UTE) MR imaging has been used successfully for isotropic high-spatial-resolution morphologic lung imaging in small-animal studies (13)(14)(15)(16)(17)(18). Previous studies in human subjects have used relatively thick-section two-dimensional UTE breath-hold sequences with limited spatial coverage (19)(20)(21).…”
Section: Animal Modelmentioning
confidence: 99%